IMPROVEMENT OF SEED PRODUCTION AND QUALITY GROUPER BY HYBRIDIZATION PROGRAM - Suko Ismi; Yasmina Nirmala Asih; Daniar Kusumawati (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2013)
Several types of grouper hybrid seeds can now be massively produced in a hatchery. Hybrid seeds can increase diversification of aquaculture species and potential to increase fish production.  Therefore, an  improvement in hybrid seed production both in high quantity and quality is very important. This research was conducted to produce massively cantik grouper hybrid seeds i.e.,a crossbreed between female tiger grouper (Epinephelus fuscoguttatus) and male marbled grouper (Epinephelus microdon). This research examined the cantik grouper seed production compared with the production of tiger grouper and marbled grouper fingerlings. The research results showed that cantik hybrid grouper seeds production had higher survival rate (24.59%) than tiger grouper (17.44%) and marbled grouper (4.63%). The total length of the seed at the age of 45 days for cantik grouper  was 3.59 ± 0.21 cm, tiger 3.24 ± 0.55 cm, and batik 2.61 ± 0.42 cm, respectively. Seed abnormality for cantik grouper was 4.13%, tiger grouper 30.21%, and marled tiger 0.57%, respectively. Based on genetic variation analyses, the cantik grouper had a closer genetic relationship with the marbled grouper compared with the tiger grouper. Keywords: Marbled grouper, hybridization program, seeds production, quality